HUBUNGAN ANTARA DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN HOMESICKNESS PADA MAHASISWA RANTAU JURUSAN ILMU PENDIDIKAN ANGKATAN 2024 DI UNIVERSITAS JAMBI - Pakpahan, Ipa; Elfira, Ninil; Wahyuni, Hera (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Overseas students often face difficulties in adapting to a new environment which may lead to homesickness, a feeling of longing for home and family. This condition can affect students’ psychological well-being and learning process. One factor that may reduce homesickness is peer social support. This study aims to determine the relationship between peer social support and homesickness among overseas students of the Department of Education, Class of 2024 at Universitas Jambi. This research used a quantitative approach with a correlational design. The population consisted of 197 students, with a sample of 108 students selected using purposive sampling. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability. Data analysis used the Pearson Product Moment correlation test with SPSS 26. The results showed that peer social support was in the high category (82.85%), while homesickness was in the low category (66.44%). The correlation test showed a significance value of 0.000 < 0.05 with a correlation coefficient of 0.566, indicating a significant relationship with a moderate category.